An investigation into the effects of clinical facilitator nurses on medical wards - Whitehead, William (2010)
This thesis investigates the effects of clinical facilitator nurses on medical wards in hospitals. These staff are the current culmination of recent attempts to situate nurse education in the field of clinical practice rather than merely the lecture room. Therefore, the work sets out to gain an understanding of the clinical and educational needs perceived by policy makers; the methods chosen by local managers to fulfil these needs; and the practical manifestation of these initiatives at the bedside. The thesis commences with a literature review consisting of historical context studies and a focused analysis of recent research literature. The context studies are of adult and nurse education. The review of clinical facilitator literature uses search criteria to identify and critically analyse previous research related to similar roles in the United Kingdom. The researcher uses a modified grounded theory approach as a methodological framework for collection and use of data. The data is obtained primarily by field observations; semi-structured interviews with practising clinical facilitators; and from questionnaires completed by nursing students. In addition to this generated data, information harvested from official and academic sources is used to produce theory. The discussion chapter explores the contestation that the themes generated indicate that the introduction of educationally focussed staff, into the area dominated by clinical need, is both problematic and essential. Problematic, as conflicts of role and leadership create misunderstanding and hardship for educators and clinicians. Essential, because in acute wards, where nursing skill is literally a matter of life or death for patients, a large proportion of nursing staff are in need of focussed educational support. The study proposes a model of managerial support for the introduction of educationally focused nurses in the clinical area which enables these clinical facilitators to operate in a valued and protected position.